Ferroptosis: A new insight for treatment of acute kidney injury - Li, Shiyang; Wang, Rui; Wang, Yixue; Liu, Yong; Qiao, Yingjin; Li, Peipei; Chen, Jingfang; Pan, Shaokang; Feng, Qi; Liu, Zhangsuo; Liu, Dongwei (Frontiers in Pharmacology, 2022)
Acute kidney injury (AKI), one of the most prevalent clinical diseases with a high incidence rate worldwide, is characterized by a rapid deterioration of renal function and further triggers the accumulation of metabolic waste and toxins, leading to complications and dysfunction of other organs. Multiple pathogenic factors, such as rhabdomyolysis, infection, nephrotoxic medications, and ischemia-reperfusion injury, contribute to the onset and progression of AKI. However, the detailed mechanism remains unclear. Ferroptosis, a recently identified mechanism of nonapoptotic cell death, is iron-dependent and caused by lipid peroxide accumulation in cells. A variety of studies have demonstrated that ferroptosis plays a significant role in AKI development, in contrast to other forms of cell death, such as apoptosis, necroptosis, and pyroptosis. In this review, we systemically summarized the deﬁnition, primary biochemical mechanisms, key regulators and associated pharmacological research progress of ferroptosis in AKI. We further discussed its therapeutic potential for the prevention of AKI, in the hope of providing a useful reference for further basic and clinical studies.